2018
DOI: 10.1111/hepr.13275
|View full text |Cite
|
Sign up to set email alerts
|

Stevia prevents experimental cirrhosis by reducing hepatic myofibroblasts and modulating molecular profibrotic pathways

Abstract: Aim The aims of the present study were to investigate the capacity of stevia leaves to prevent experimental cirrhosis induced by chronic administration of carbon tetrachloride (CCl4) in rats and to explore the action mechanism involved. Methods Liver cirrhosis was established by CCl4 treatment (400 mg/kg i.p. three times a week for 12 weeks); stevia powder was administered (100 mg/kg by gavage daily) during the CCl4 treatment. Serum markers of liver damage and hydroxyproline were evaluated and histopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…During chronic liver injury, activation of quiescent HSCs is a necessary step to promote the expression of ECM proteins, which ultimately leads to fibrosis. In this regard, our present results indicate that one of the beneficial mechanisms of Reb A in inhibiting the development of fibrosis is the prevention of HSC activation; this observation is consistent with our previous observations that stevia leaves prevent experimental cirrhosis and modulate profibrogenic pathways mainly by blocking HSCs (Ramos‐Tovar, Buendia‐Montaño, et al, ; Ramos‐Tovar, Flores‐Beltrán, et al, ). The present results showed that Reb A exerted an antifibrogenic effect when coadministered with the profibrogenic agent TAA, maintaining the deposition of collagen in the liver parenchyma.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During chronic liver injury, activation of quiescent HSCs is a necessary step to promote the expression of ECM proteins, which ultimately leads to fibrosis. In this regard, our present results indicate that one of the beneficial mechanisms of Reb A in inhibiting the development of fibrosis is the prevention of HSC activation; this observation is consistent with our previous observations that stevia leaves prevent experimental cirrhosis and modulate profibrogenic pathways mainly by blocking HSCs (Ramos‐Tovar, Buendia‐Montaño, et al, ; Ramos‐Tovar, Flores‐Beltrán, et al, ). The present results showed that Reb A exerted an antifibrogenic effect when coadministered with the profibrogenic agent TAA, maintaining the deposition of collagen in the liver parenchyma.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated the pharmacological properties of Stevia rebaudiana Bertoni as a hepatoprotector and mainly as an antifibrotic agent (Ramos‐Tovar, Buendia‐Montaño, et al, ; Ramos‐Tovar, Flores‐Beltrán, et al, ; Ramos‐Tovar, Hernández‐Aquino, et al, ). However, few studies have been performed to evaluate the related pharmacological effects of its secondary compounds, such as Reb A (Holvoet et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found that stevia leaves powder inhibited chronic liver damage induced by CCl 4 administration by reducing hepatic myofibroblasts and modulating some molecular profibrotic pathways . Herein, we found that SVT, a diterpenoid present in stevia leaves, inhibited liver cirrhosis induced by TAA in rats by modulating MMPs, inhibiting the activation of HSCs, down‐regulating TGF‐β1 and the canonical and non‐canonical Smad pathways.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have been performed to investigate the effects of various antioxidants on different models of liver damage and have shown the causative role of ROS in the profibrogenic process. In models of bile duct ligation-, CCl 4 -, and thioacetamide chronic intoxication-induced fibrosis in rodents and in vitro studies, several compounds with direct or indirect antioxidant activity have been shown to prevent or reverse the accumulation of extracellular matrix (ECM) proteins (fibrotic tissue) within the hepatic parenchyma or the production of profibrogenic genes or proteins [59][60][61][62][63][64][65][66][67][68][69][70][71][72]. One of the most studied phytodrugs with important antioxidant properties is silibinin, the main active constituent of silymarin [73].…”
Section: Attenuating Oxidative Stress Produces An Antifibrotic Effectmentioning
confidence: 99%